EVALUASI HASIL INVESTIGASI KONTAK ERAT PASIEN TUBERKULOSIS OLEH KADER AISYIYAH PADA LAPORAN TRIWULAN 4 TAHUN 2018 DI KOTA MEDAN - FARIDA UTAMI SIREGAR; ISTI ILMIATI FUJIATI (LP2MTBM MAKARIOZ, 2021)
This research used a descriptive method with cross sectional design. Subjects were all household contacts and close contactwith TB patients in 18 sub-districts in Medan. The sampling by total sampling technique. Suspected TB was found from thehighest rate based on age at 45-60 years old (27.4%), age > 60 years old (27.4%), age 21-35 years old (16.7%), age 36-45years old ( 14.4%), based on gender was found that the male was higher (59.2%). Based on the symptoms was found thatthe cough was higher (84.6%), based on the risk factor was found that the smokers were higher (35.1%). From the researchresults, it was found that the subject of the research was a TB index of 565 people with an index contact number of 11,034people. Base on age, it was found that the elderly and productive age, base on the gender, it was found in male, base on thesymptom, it was found that coughing and based on the risk factor was smoking.